2017
DOI: 10.3389/fphy.2017.00061
|View full text |Cite
|
Sign up to set email alerts
|

Design and Validation of Diffusion MRI Models of White Matter

Abstract: Diffusion MRI is arguably the method of choice for characterizing white matter microstructure in vivo. Over the typical duration of diffusion encoding, the displacement of water molecules is conveniently on a length scale similar to that of the underlying cellular structures. Moreover, water molecules in white matter are largely compartmentalized which enables biologically-inspired compartmental diffusion models to characterize and quantify the true biological microstructure. A plethora of white matter models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
212
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(231 citation statements)
references
References 183 publications
(227 reference statements)
5
212
1
1
Order By: Relevance
“…Though smaller values of D e∥ were seen with Method 2 in Region II, the large estimation error warns against relating this to underlying pathology. The accuracy of diffusivities in this study is also questionable in view of recent evidence that suggested D a ≥ D e∥ and D a ≈ 1.9‐2.2 μm 2 /ms . Though D a by Method 2 was close to the expected range, the observed D a ≤ D e∥ trend possibly indicates that our estimation might have fallen into the wrong branch or some spurious local minima due to the low maximum b ‐value and SNR.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Though smaller values of D e∥ were seen with Method 2 in Region II, the large estimation error warns against relating this to underlying pathology. The accuracy of diffusivities in this study is also questionable in view of recent evidence that suggested D a ≥ D e∥ and D a ≈ 1.9‐2.2 μm 2 /ms . Though D a by Method 2 was close to the expected range, the observed D a ≤ D e∥ trend possibly indicates that our estimation might have fallen into the wrong branch or some spurious local minima due to the low maximum b ‐value and SNR.…”
Section: Discussioncontrasting
confidence: 73%
“…To date, many such models have been proposed and used in clinical and experimental studies . However, it is emphasized that so far no definite consensus has been reached on how to parameterize the complex brain microstructure . Besides, works by Jelescu et al, Novikov et al, and Reisert et al demonstrated that typical DKI acquisition with a maximum b ‐value of 2000‐3000 s/mm 2 is not sufficient to determine all of the parameters, even for a simple two‐compartment model.…”
Section: Introductionmentioning
confidence: 99%
“…In microstructural models for white matter based on dMRI data, differences in the intra‐axonal and extra‐axonal T 2 values have typically been ignored . This is understandable, considering that the daunting task of linking brain microstructure to dMRI data necessitates simplifying assumptions to obtain a tractable mathematical description capable of yielding useful predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Other algorithms, and possibly multi‐channel fluorescence microscopy data, will be required to identify the biophysical changes that account for the observed spatial variation of response functions in the brain. In principle, knowledge of the relevant biophysical parameters would allow calculation of the local response function—see Reference for a review of the challenges and recent progress in diffusion MRI modeling.…”
Section: Discussionmentioning
confidence: 99%